Oxynoemacheilus sarus, a new nemacheilid loach from the lower Ceyhan and Seyhan in southern Anatolia (Teleostei: Nemacheilidae) - Freyhof, Jörg; Yoğurtçuoğlu, Baran; Kaya, Cüneyt (Zootaxa, 2021)
Oxynoemacheilus sarus, new species, is described from the lower Ceyhan and Seyhan drainages in southern Anatolia. It is distinguished from other Oxynoemacheilus species in Cilicia (including the Göksu, Seyhan and Ceyhan drainages) by possession of a series of irregularly shaped midlateral blotches, 3–5 dark-brown bands on the caudal fin, a complete lateral line, a forked caudal fin (shortest middle caudal-fin ray is 56–70% of longest ray of the upper caudal-fin lobe), the caudal peduncle depth 1.4–1.8 times in its length, and a suborbital groove in male individuals. The new species occurs in sympatry with superficially similar O. seyhanicola and O. evreni, and is distinguished by colour pattern as well as morphometric and molecular characters. Molecular data suggest that the closest relatives to the new species in our dataset are O. euphraticus and O. shehabi, which is characterised by a minimum K2P distance of 3.6% and 3.8%, respectively, in the COI mtDNA barcode region.